Effects of a subconvulsive dose of kainic acid on the gene expressions of the arginine vasopressin, oxytocin and neuronal nitric oxide synthase in the rat hypothalamus. (October 2015) - Yoshimura, Mitsuhiro; Ohkubo, Jun-ichi; Hashimoto, Hirofumi; Matsuura, Takanori; Maruyama, Takashi; Onaka, Tatsushi; Suzuki, Hideaki; Ueta, Yoichi
Highlights: The present study used a subconvulsive dose of kainic acid (4 mg/kg) in rats. AVP heteronuclear RNA was significantly increased in kainic acid-treated rats. The oxytocin and nNOS gene expressions were up-regulated in kainic acid-treated rats. The hypothalamic peptides synthesis may be differentially affected by kainic acid. Abstract: Arginine vasopressin (AVP) synthesis in the hypothalamo-neurohypophysial system (HNS) is up-regulated by kainic acid (KA)-induced seizure in rats. However, it remains unknown whether a subconvulsive dose of KA affects the HNS. Here we examined the effects of subcutaneous (s.c.) administration of a low dose of KA (4 mg/kg) on the gene expressions of the AVP, oxytocin ( OXT ) and neuronal nitric oxide synthase ( nNOS ) in the supraoptic (SON) and paraventricular nuclei (PVN) of the rat hypothalamus, using in situ hybridization histochemistry. The expression of the AVP gene in the SON and PVN was judged to be up-regulated in KA-treated rats in comparison with saline-treated rats as controls. Next, the expression of the OXT gene was significantly increased in the SON at 6–24 h and in the PVN at 6 and 12 h after s.c. administration of KA. Finally, the expression of the nNOS gene was significantly increased in the SON and PVN at 3 and 6 h after s.c. administration of KA. These results suggest that up-regulation of the gene expressions of the AVP, OXT and nNOS in the rat hypothalamus may be differentially affected by peripheral administration of a subconvulsive dose of KA.